TRANSFORMASI NILAI-NILAI RELIGIUS DALAM ERA DIGITAL KAJIAN SOSIOLOGI AGAMA - Siregar, Ahmad Parwis (UIN Sumatera Utara Medan, 2026)
The development of information and communication technology has driven profound transformations in various aspects of social life, including in the realm of religion. This article aims to analyze changes in religious values in the midst of a digital society through a sociology of religion approach. This approach is used to understand how values such as sincerity, simplicity, solidarity, and spirituality experience changes in form, delivery, and meaning, especially due to the penetration of social media, digital platforms, and modern communication technology. This study uses a qualitative approach with literature studies and phenomenological observations of digital religious content in Indonesia. The results of the study show that the transformation of religious values does not only occur in the form of digital mediation, but also in the formation of new religious authorities, symbolic changes, and the commodification of religious values. The phenomena of digital preaching, celebrity ustaz, and online hijrah culture reflect how religion is no longer just a spiritual value system, but also becomes part of social performativity and digital identity. On the other hand, online religious spaces also open up opportunities for the emergence of more inclusive and cross-geographical religious communities. This study recommends the importance of religious digital literacy and the active involvement of religious institutions in guiding people to adhere to the basic values of religion amidst the rapid and complex flow of digital transformation.